2021
DOI: 10.1158/1078-0432.ccr-21-2639
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evidence in Support of Oncology Product Registration: A Systematic Review of New Drug Application and Biologics License Application Approvals from 2015–2020

Abstract: BA, AN, and BW are employees of and own stock for Pfizer, Inc. MSD, RHB, MD, LH, and MW are employees of Analysis Group, Inc., a consulting company that has received research funding from Pfizer, Inc. KW and JW were employees of Analysis Group during the conduct of the study. GDD received consulting fees from Pfizer, Inc., and is an employee of Dana-Farber Cancer Institute, which has grants and/or contracts with Pfizer, Inc.Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…With the recent and rapid adoption of electronic health records (EHR) to document patient information at the point of care, real-world data (RWD) have become a viable source of clinical information (1). Since the passing of the 21st Century Cures Act into law to accelerate medical development and bring innovations faster and more efficiently to patients (2), greater focus has emphasized the use of real-world evidence to help inform treatment effectiveness and regulatory decisions (3,4). In certain instances when randomization to a control arm is either unethical or infeasible, RWD have supported drug approval (3) or label expansion (5) decisions.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent and rapid adoption of electronic health records (EHR) to document patient information at the point of care, real-world data (RWD) have become a viable source of clinical information (1). Since the passing of the 21st Century Cures Act into law to accelerate medical development and bring innovations faster and more efficiently to patients (2), greater focus has emphasized the use of real-world evidence to help inform treatment effectiveness and regulatory decisions (3,4). In certain instances when randomization to a control arm is either unethical or infeasible, RWD have supported drug approval (3) or label expansion (5) decisions.…”
Section: Introductionmentioning
confidence: 99%
“…A first systematic review evaluated oncological new drug applications and biologics license application between 2015 and 2020 [ 34 ] and found that, among other results, already 11 among 133 oncology new therapy approvals utilized RWE to support the efficacy of the drugs. The review concluded “that real-world studies used as external controls complemented efficacy data from single-arm trials in successful oncology product approvals, and that the key attributes identified include early engagement, a priori protocol development, and robust research design” [ 34 ]. Given the help of RWE research, the utility and application of cancer therapies can be studied, e.g., in second- or third-line treatment where several equivalent options exist.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the number of applications including RWE as supporting evidence to both the US FDA and the EMA has increased [ 11 , 12 ]. At the same time, the number of approvals where RWE influenced regulatory decision making and was included in product labels has also increased [ 12 , 13 ], highlighting the emerging role of RWE in the regulatory decision-making process. The potential role of RWE on cost-effectiveness analyses has also been highlighted as a valuable aspect that could impact health technology assessment decisions [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%